2010
DOI: 10.1080/17470211003703475
|View full text |Cite
|
Sign up to set email alerts
|

Judgements of time to contact are affected by rate of appearance of visible texture

Abstract: More fine-grained texture becomes visible if the distance between an observer and an object or surface is reduced. This article illustrates with a schematic example that the inverse rate of the relative appearance of visible texture provides information about time to contact if the observer has a constant visual acuity and the texture has a certain scale-independent structure. An experiment is reported in which texture appearance was manipulated. Participants were asked to make forced-choice time-to-contact ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Furthermore, disambiguating the contribution of different visual cues that are inherently linked to a looming object is a challenging next step. In this experiment, we controlled for global changes in luminance using point light stimuli, but manipulating object properties such as visible texture can bias the percept of looming [27]. …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, disambiguating the contribution of different visual cues that are inherently linked to a looming object is a challenging next step. In this experiment, we controlled for global changes in luminance using point light stimuli, but manipulating object properties such as visible texture can bias the percept of looming [27]. …”
Section: Discussionmentioning
confidence: 99%
“…An alternative version of our device [23,24] actually used different driving voltages (and hence, different intensities) for different actuators, with driving voltage being a function of distance. In vision it has been shown that fine-grained texture is exploitable for TTC perception, in addition to the main role of the tau-component defined by the outline of the approaching object [30]. Although the device presented in this study is able to regulate the intensity of the actuators, we used this type of regulation only in one of our experiments: the more informal one with a ballhitting task.…”
Section: Embodiment and Sensory Substitutionmentioning
confidence: 99%
“…We have developed a classic perceptual experiment designed to study TTC (cf. [30]). In this procedure, a sphere approaching the participant at a constant speed was simulated and presented visually on a screen and/or as a tactile stimulation through the waistband.…”
Section: Software For Simulated Environmentsmentioning
confidence: 99%
“…Behaviorally speaking, however, a bulk of recent evidence casts doubts on the use of τ as a general model for TTC estimation. Deviations from τ predictions have been reported depending on the type of task (Lugtigheid and Welchman, 2011), the duration of the trajectory (Hosking and Crassini, 2011), illusory or contextual effects (Smeets et al, 1996; DeLucia et al, 2000), texture (Jacobs and Diaz, 2010) or reliability of physical information relevant for catching like ball size (López-Moliner et al, 2007b; López-Moliner and Keil, 2012) or shape (López-Moliner et al, 2007a). …”
Section: Introductionmentioning
confidence: 99%